Theoretical study on the reaction mechanism of DMFC and DFAFC facilitated by palladium-based catalysts - Yang, Jing (2012)
Electrocatalytic surface reaction has attracted more and more interests from both the experimental and the theoretical researchers. It is of great significance to have a deep insight of the mechanism of the reaction in the electrochemistry system. The mechanism of direct methanol fuel cell (DMFC) catalyzed by palladium electrode under both neutral and alkaline condition is theoretically studied. Under neutral condition, the energy barrier for the first dehydrogenation of CH3OH via either C–H bond scission or O–H bond scission is very high which leads to the palladium shows very low activity towards methanol decomposition under neutral condition. However, under alkaline condition the reaction barrier of the O–H bond scission of CH3OH is effectively reduced by the adsorbed OH and gives out the first intermediate, CH3O. The further reaction via CH2O and HCO to CO and then the CO combines with the adsorbed OH to COOH. And the COOH directly accounts for the final product of CO2. This reaction mechanism is in line with the reported experimental results. The direct formic acid fuel cells (DFAFCs) are regarded as one of the most promising alternative to H2 and alcohol based fuel cells and they have attracted great interest in the past decades. However, the reaction mechanism of DFAFCs with metal surface as the electrolytes is still unclear. Even the experimental results have given the controversial phenomena. We proposed three reaction mechanisms to analysis the experimental phenomena. Four possible adsorption geometries of the adsorbed formic acid are selected as the initial reactant. The hydrogen centered formic acid and the oxygen and hydrogen centered formic acid accounts for the direct pathway. The oxygen and hydrogen centered formic acid and the oxygen centered formic acid will lead to the reaction pathway where the formate serves as an intermediate. And the oxygen and hydrogen centered formic acid, the oxygen centered formic acid and the bi-oxygen centered formic acid contributed to the formate which serves as the site blocking species. Finally, to make the study more systematic, we have carried out the research of catalyst design. We aim to design the palladium based catalyst through the sublayer structure. By the examination of the electronic structure of the Pd(1 1 1) surface with sublayer structure, we have revealed that its Fermi-energy level, the d-band center and the work function can be adjusted by the verification of the sublayer structure. Based on Brønsted–Evans–Polanyi (BEP) relation, Sabatier principle, work function theory and the d-band theory, we propose the possibility of the new palladium based catalyst.